2022
DOI: 10.3390/insects13070569
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Rich Field Margins Influence Natural Predators of Aphids More Than Intercropping in Common Bean

Abstract: Field margins support important ecosystem services including natural pest regulation. We investigated the influence of field margins on the spatial and temporal distribution of natural enemies (NEs) of bean pests in smallholder farming systems. We sampled NEs from high and low plant diversity bean fields using sweep netting and coloured sticky traps, comparing monocropped and intercropped farms. NEs collected from within crops included predatory bugs, lacewings, predatory flies, parasitic flies, parasitic wasp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Finding similar to this current study have showed that border crop integrated with other management system can effectively suppressed insect pest population and the subsequent damage effect on plants [ 27 , 29 ]. Border cropping approach is thought to effectively reduce aphid population by distracting pests to other crops not primary and attracting their natural enemies, reducing the target pest population and economic loss impact on the crop while enhancing biological control [ 43 ]. Unlike, the extra shelter and floral resources for insect pests and/or predators boosting ecosystem services functionality at the border crop system.…”
Section: Discussionmentioning
confidence: 99%
“…Finding similar to this current study have showed that border crop integrated with other management system can effectively suppressed insect pest population and the subsequent damage effect on plants [ 27 , 29 ]. Border cropping approach is thought to effectively reduce aphid population by distracting pests to other crops not primary and attracting their natural enemies, reducing the target pest population and economic loss impact on the crop while enhancing biological control [ 43 ]. Unlike, the extra shelter and floral resources for insect pests and/or predators boosting ecosystem services functionality at the border crop system.…”
Section: Discussionmentioning
confidence: 99%
“…The finding is in line with results of the cage experiment where B. pilosa and G. parviflora supported emergence of high number of live parasitoids. Presence of nectar and pollen in these plants have been documented to significantly increase the activity, longevity and fecundity of predators and parasitoids (Bianchi & Wäckers, 2008; Ndakidemi et al, 2022; Parajulee et al, 1994). Conversely, Tagetes minuta showed little evidence of use by natural enemies captured from the crop, in contrast to other studies recording beneficial insect interactions with this plant (Souza et al, 2019).…”
Section: Discussionmentioning
confidence: 99%